37. KNOWLEDGE AND PRACTICE OF CARING FOR INSTRAVENTRICULAR CATHETERS OF NURSES AT THANH NHAN HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe nurses' knowledge and practice in central venous catheter (CVC) care and identify factors associated with their knowledge and practice at Thanh Nhan Hospital in 2024.Methods: A cross-sectional study was conducted among 100 nurses from four departments: Internal Emergency, External Emergency, Surgical Intensive Care, and Critical Care.Results: The average knowledge score was 7.8 (range: 5–9), with 83,0% of nurses meeting the required knowledge standards, while 17,0% failed, particularly in identifying early complications. The average practice score was 15.20 (range: 0–26), with 34,0% failing to meet standard procedural requirements, and no nurses achieving the maximum score. A relationships were found between gender and education level with both knowledge and practice classification in CVC care (p < 0.05). Nurses with less than five years of experience in intensive care, as well as those younger than 30 or older than 50, had lower scores of CVC care.Conclusion: The proportion of nurses meeting the required standards in CVC knowledge and practice remains low. Special attention should be given to training female nurses and those with limited intensive care experience while also reinforcing knowledge updates and refresher training for nurses over 50 years old. Regular training interventions and advanced professional development programs are recommended to enhance the clinical competence of the nursing workforce.
Keywords: catheter care; knowledge; practice; nurses; Thanh Nhan hospital.